Comparison of the standing balance between pole vaulters and soccer players in preseason and postseason - Katarzyna Dmitruk; Małgorzata Gałązka; Mirosława Cieślicka; Dariusz Soszyński; Robert Stępniak; Mariusz Klimczyk; Sergii S. Iermakov (Physical Education of Students, 2020)
Background and Study Aim: Static is crucial in the maintaining the position of the body’s center of gravity vertically over the base of support. Many sport disciplines require effective balance system. However, the efficiency of the system differs based on the sport discipline. The aim of the study was to examine balance system efficiency in pole vaulters and soccer players. Additionally, the analysis of pre and postseason balance system efficiency was performed in pole vaulters and soccer players as well.